Isoniazid induced childhood diabetes: A rare phenomenon - Manish, Gutch (J Basic Clin Pharm, 2015)
Drugs raise blood glucose concentrations via two broad mechanisms: By reducing insulin biosynthesis or secretion, or by reducing tissue sensitivity to insulin. Until date, there have been very few reported cases of isoniazid induced diabetes. We are presenting a case report of 6-year-old child with isoniazid induced diabetes who was misdiagnosed initially as a case of type 1 diabetes mellitus. We hereby stress that before diagnosing a patient with diabetes-type 1 or 2, a detailed history of drug intake for any such drugs, which can cause hyperglycemia has to be taken. Clear cut knowledge/cognizance of all such culprit drugs is therefore required.